Regulación del financiamiento participativo financiero —crowdfunding— en el Perú: ¿Estamos cometiendo el error de siempre? - Tovar Ayllón, Adrian (2021)
In this article, the author makes a criticism of the Crowdfunding Law Regulation Project. The author starts from the premise that, although it is not strictly necessary to approve special regulations for this activity to be carried out successfully, adequate regulation can contribute to its development by strengthening the trust of the investing public in the Recipients and Management Companies participating in the market. However, he arrives at the conclusion that the Draft Regulation suffers from what it labels as a “common mistake”, that is, it is an excessive regulation that seeks to protect the investor to the detriment of the development and growth of the regulated activity. The author ends by calling for the approval of flexible regulations and greater trust in the functioning of the market.